PKE UiTMCPP and NI Malaysia Sdn Bhd (now part of Emerson) collaborate to establish NI embedded system lab / Abdul Malek Saidina Omar, Nor Azlan Othman and Nor Salwa Damanhuri - Saidina Omar, Abdul Malek; Othman, Nor Azlan; Damanhuri, Nor Salwa (PKE, UiTMCPP, 2024)
On 26 August 2024, Universiti Teknologi MARA (UiTM) Penang Branch, through its Electrical Engineering Studies, took a significant step in advancing engineering education by partnering with NI Malaysia Sdn Bhd, now part of Emerson. This collaboration was formalized through a Memorandum of Agreement (MoA) to establish the NI Embedded System Lab, a state-of-the-art facility valued at MYR364,434.00 (USD77,539.15). The lab is equipped with advanced tools like LabVIEW, Multisim software, and MyRIO devices, aimed at enhancing students' skills in electrical and electronics engineering.